Det kæmpende Danmarks radiostudie og film - Thing, Morten (Arbejderhistorie, 2012)
Morten The Fighting Denmark`s Radio and Film Studio, Arbejderhistorie 1/2012, s. 14-30. In connection to the sabotage organization in late 1944 a little group was built up which called itself the Fighting Denmark`s Radio and Film Studio. The group produced recordings which were etched onto gramophone records. The recordings were about the resistance movement in Denmark and the records were transmitted on the BBC`s Danish service. A single direct reportage from a sabotage action was produced by the group, which was a great hit with the BBC. In last months of the war the group also produced a film. Rigmor Kaplan was leader while the journalist Kaj Christiansen acted as the voice of the group.